Composition and preparation method of fluid loss agent capable of resisting ultra-high temperature of 240 DEG C

Through the use of quaternary polymerization technology and crosslinking agents, high-temperature and salt-resistant water-reducing agents are prepared, which solves the problem of failure of the existing technology in high-temperature and high-salt environments, and realizes the stability and water-reducing effect of cement slurry, reduces costs and adapts to the demand for ultra-high-temperature cementing.

CN120248214APending Publication Date: 2025-07-04CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510424588.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing water-reducing agent fails in a high-temperature and high-salt environment, resulting in the loss of cement slurry filtration, affecting the quality of cementing and may lead to problems such as oil and gas layer pollution and troughs. The existing technology has high cost and poor dispersion, making it difficult to promote in oil fields.

Method used

Using quadruple polymerization technology, crosslinking agent is introduced, and water-soluble monomers such as 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, acrylic acid, N,N-dimethacrylamide and N,N-methylenebisacrylamide are prepared by aqueous solution polymerization to form a crosslinking network structure to improve temperature and salt resistance.

Benefits of technology

In a high-temperature environment, it significantly reduces the water loss of cement slurry, improves suspension stability, reduces costs, adapts to ultra-high temperature cementing needs, and has no significant impact on other properties of cement slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248214A_ABST
    Figure CN120248214A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultrahigh-temperature fluid loss agent for well cementation, and belongs to the technical field of oilfield chemistry. The synthetic monomers of the fluid loss agent comprise 2-acrylamide-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), acrylamide (AM), N, N-dimethylacrylamide (DMAM), N, N-methylene bisacrylamide (MBA), a structural unit A as shown in a formula 1, a structural unit B as shown in a formula 2, a structural unit C as shown in a formula 3, a structural unit D as shown in a formula 4 and a structural unit E as shown in a formula 5. The fluid loss agent has excellent temperature resistance and salt tolerance, and has excellent fluid loss reduction performance in both high-temperature and ultra-high-temperature environments, and the fluid loss volume at 240 DEG C is 1t; the fluid loss agent has no obvious influence on the basic performance of the cement paste, can effectively improve the suspension stability of the cement paste at high temperature, and is suitable for being used as the fluid loss agent of the cement paste for well cementation at ultrahigh temperature. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of applied chemistry of drilling and completion fluids, and specifically relates to a composition of a super-high temperature fluid loss reducer for cementing and a preparation method of a super-high temperature fluid loss reducer. Background Art

[0002] Petroleum is one of the indispensable non-renewable resources in modern society, and its exploitation and utilization play an important role in the development of the national economy. At present, with the continuous exploitation of oil and gas, it has gradually changed from conventional oil and gas to deep reservoirs. For deep reservoirs, there are still many problems to be solved in the exploitation process. Cementing is an essential and important part of oil and gas exploration and development, an important link in drilling engineering, and a key step to ensure the life of oil and gas wells, improve the productivity of oil and gas wells, and promote the overall efficiency of oil and gas exploration and development. For deep and ultra-deep cementing technologies, they face problems such as high temperature, high pressure, complex formations, loss of circulation, salt gypsum layers, and long cementing intervals. Compared with conventional well sections, the cementing difficulty increases significantly, which also requires cementing additives to have better performance to cope with this harsh environment.

[0003] Retarders, fluid loss reducers, and dispersants are the three main agents in the oil well cementing project, and play a crucial role in the comprehensive performance of cement slurries, the safety guarantee of the cementing process, and the cementing quality. Among them, fluid loss reducers can effectively control the filtration loss of cement slurries into the formation. However, in deep well and ultra-deep well environments, especially after 200 °C, conventional fluid loss reducers are extremely prone to hydrolysis, chain breakage, etc. and become ineffective in such environments, resulting in out-of-control filtration loss of cement slurries. The out-of-control filtration loss will not only cause adverse effects such as oil and gas layer pollution, formation damage, and channeling, but also affect the cementing quality, and in severe cases, it will cause cementing accidents and cementing failures. Since most of the conventional linear polymers of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) have a maximum service temperature of not more than 180 °C, and have poor sedimentation stability and a great impact on the rheology of cement slurries, they cannot meet the requirements of cementing in high-temperature and high-salt environments. Therefore, there is an urgent need to provide a fluid loss reducer that can work stably in high-temperature and high-salt environments and has excellent comprehensive performance.

[0004] Chinese patent document CN 113651931A discloses a preparation method of a super-high temperature modified polymer-based cement filtrate reducer. The preparation method is as follows: First, graphene oxide is ultrasonically dispersed and then reacted with azobisisobutyramidine hydrochloride in an alkaline environment. Then, 2-acrylamido-2-methylpropanesulfonic acid, N,N-dimethylacrylamide, and itaconic acid are used as polymerization monomers to react with the treated graphene solution to synthesize a super-high temperature modified polymer-based cement filtrate reducer, which has the advantages of stable performance, strong temperature resistance (30 - 240 °C), salt resistance up to saturation, excellent filtrate reduction performance, strong adaptability, and significantly improving the mechanical properties of cement stone. However, due to the high price of graphene oxide and the difficulty in dispersing the modified product, it is difficult to promote it in the oilfield.

[0005] Chinese patent document CN 115404061A discloses a preparation method of a high-temperature and salt-resistant cement filtrate reducer composition. An intermediate polymer is formed from an alkaline monomer and a neutral monomer. The alkaline monomer is mainly one or more of para-, ortho-, and meta-vinyl sulfonates containing a benzene ring, and the neutral monomer is a mixture of acrylamide and lauryl methacrylate in any proportion. Ammonium persulfate is used as an initiator. After the reaction is completed, an acidic monomer solution such as acrylic acid is slowly dropped in and the reaction continues to form a block copolymer. The resulting copolymer can effectively reduce the water loss of the cement slurry and has little effect on the rheological properties of the cement slurry. However, its water loss performance above 120 °C has not been tested, and it is impossible to determine whether it is suitable for high-temperature environments.

[0006] Chinese patent document CN 118620136A discloses a cement filtrate reducer for well cementing and its preparation method. The preparation method is as follows: 2-acrylamido-2-methylpropanesulfonic acid is used as a polymerization monomer to react with a copolymer of N-vinylpyrrolidone and acrylic acid to synthesize a cement filtrate reducer for well cementing, which has the advantages of stable performance, strong temperature resistance, excellent filtrate reduction performance, strong adaptability, and significantly improving the mechanical properties of cement stone. However, due to the difficulty in controlling the molecular weight of the copolymer and the difficulty in dispersing the modified product, it is difficult to promote it in the oilfield.

[0007] Although the cement filtrate reducers in the prior art represented by the above patents have made breakthroughs in terms of temperature resistance and salt resistance of polymer-based cement filtrate reducers, there are still problems in the application and promotion of ultra-high temperature well cementing operations above 200 °C. Summary of the Invention

[0008] Aiming at the deficiencies of poor temperature and salt resistance and high cost of particulate materials in the prior art, the present invention provides a preparation method of a super-high temperature fluid loss reducer for cementing. The fluid loss reducer is prepared with the quaternary polymerization technology as the core, and a cross-linking agent is introduced for micro-crosslinking to improve the high-temperature resistance and filtration control ability of the fluid loss reducer, which can effectively improve the temperature and salt resistance of the polymer, reduce the water loss of the cement slurry in high-temperature and ultra-high temperature environments, and improve the suspension stability of the cement slurry.

[0009] The present invention uses the quaternary polymerization technology and introduces a cross-linking agent. Water-soluble monomers such as 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, acrylic acid, N,N-dimethylacrylamide, and N,N-methylenebisacrylamide (MBA) are used as raw materials to prepare the polymer by aqueous solution polymerization. After testing, the product has good dispersion performance in the solution. After adding it to the cement slurry, it can significantly reduce the water loss in high-temperature and ultra-high temperature environments and improve the suspension stability of the cement slurry in high-temperature environments. The temperature resistance can reach 240 °C, and the water loss is less than 50 mL; the salt resistance can resist brine with a mass concentration of about 18%.

[0010] The preparation method of the super-high temperature fluid loss reducer for cementing is as follows: First, add 150 - 200 parts of deionized water to a ground three-necked flask, pass nitrogen for 15 - 30 minutes to remove the oxygen in the reaction liquid, add 40 - 60 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and stir and dissolve it in a stirrer. Then, weigh 3.0 - 8.0 parts by weight of acrylic acid (AA) and add it to the three-necked flask for mixing and stirring; continuously pass nitrogen, and then use a 15% NaOH solution by mass fraction to adjust the pH value of the reaction solution to 6 - 7. Weigh 15 - 25 parts by weight of acrylamide (AM), 5.0 - 8.0 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.3 - 0.5 parts of N,N-methylenebisacrylamide (MBA), and add them to the three-necked flask in sequence for mixing and stirring to obtain a mixed reaction solution. Keep stirring at a rotation speed of 200 - 400 revolutions per minute until all monomers are completely dissolved. After stirring for a certain time, a slightly viscous liquid appears to obtain a polymer gel; prepare an initiator solution, and add the initiator solution to the ground three-necked flask at a dropping rate of 5 - 10 mL / min, keep the reaction temperature at 50 °C - 60 °C, keep nitrogen passing through, and stir and react for 4 - 6 h to end the reaction; finally, naturally cool to obtain a colorless viscous liquid, which is the prepared super-high temperature fluid loss reducer.

[0011] The super-high temperature fluid loss reducer contains structural unit A shown in formula 1, structural unit B shown in formula 2, structural unit C shown in formula 3, structural unit D shown in formula 4, and structural unit E shown in formula 5;

[0012] R1, R2, R3, R4 and R5 in the constituent unit A, constituent unit B, constituent unit C, constituent unit D and constituent unit E are the same or different, and are each independently a substituted or unsubstituted alkyl group having 8 to 12 carbon atoms. The total mass of the synthetic monomers is 25% - 45% of the total mass of deionized water.

[0013] , and the initiator adopts a redox initiation system. Among them, the oxidant is at least one of persulfate, ammonium persulfate and potassium persulfate, and the reductant is at least one of sodium bisulfite and ammonium hydroxide. And the weight ratio of the amount of the oxidant to the amount of the reductant is (1 - 3):(1 - 2), and the amount of the initiator is 0.5 - 1.5% by weight of the total synthetic monomers used.

[0014] In terms of the current technology of ultra-high temperature fluid loss reducing agents for cementing, the present invention has the following advantages:

[0015] 1. The present invention is a quaternary polymer, and a cross-linking agent is introduced, which can effectively maintain the structural stability in a high-temperature environment and provide a rigid core for the polymer. After optimizing the monomer types and synthesis methods, the tolerance of the polymer itself under high-temperature conditions is enhanced. Under the combined action with different structures, the molecular volume change of the polymer is small under high temperature or high salinity. At the same time, the introduced carboxyl groups enable the product to be well adsorbed on the surface of cement particles, and the product itself can also fill the gaps in the mud cake to a certain extent. The combination of the two can form a thin and tough filter cake during the high-temperature and ultra-high temperature water loss process, so as to achieve a good water loss reduction effect in high-temperature and ultra-high temperature environments. And due to the temperature-resistant design of its own structure, the sedimentation stability of the cement slurry can also be improved in a high-temperature environment.

[0016] 2. The present invention uses AM monomer and DMAM monomer as polymerization raw materials, and introduces non-ionic segments. The AM monomer provides water solubility, and the DMAM monomer introduces hydrophobic microdomains, making the polymer have excellent amphiphilicity. The amphiphilic polymer adsorbs water through hydrophilic groups and locks water through hydrophobic groups, and the cross-linking agent MBA monomer endows the polymer with a cross-linked network structure, significantly improving the performance of the fluid loss reducing agent.

[0017] 3. The present invention regulates the high-temperature water loss performance of cement slurry for cementing in an ultra-high temperature environment by preparing an ultra-high temperature fluid loss reducing agent for cementing. It can meet the water loss reduction requirements of cement slurry for cementing in an ultra-high temperature environment.

[0018] 4. The raw materials for synthesizing this composite polymer fluid loss reducing agent are widely available, with low cost, mature synthesis conditions, and convenient use, and have very good prospects for popularization and application. Detailed implementation mode The experimental methods used in the following examples are all conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained from commercial sources without special instructions, where: In the present invention, N,N-dimethylacrylamide can be obtained by commercial purchase. For example, it can be purchased from Jiangsu Bost Chemical Technology Co., Ltd., industrial grade; acrylamide can be obtained by commercial purchase. For example, it can be purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., chemically pure; acrylic acid can be obtained by commercial purchase. For example, it can be purchased from Sinopharm Chemical Reagent Co., Ltd., chemically pure; 2-acrylamido-2-methylpropanesulfonic acid can be obtained by commercial purchase. For example, it can be purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., chemically pure; N,N-methylenebisacrylamide can be obtained by commercial purchase. For example, it can be purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., chemically pure. The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1: This example provides a high-temperature fluid loss reducer for well cementing, and its formula is: 45 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.3 parts by weight of N,N-methylenebisacrylamide (MBA). The high-temperature fluid loss reducer contains structural unit A shown in Formula 1, structural unit B shown in Formula 2, structural unit C shown in Formula 3, structural unit D shown in Formula 4, and structural unit E shown in Formula 5; Among them, R1, R2, R3, R4, and R5 in the constituent unit A, constituent unit B, constituent unit C, constituent unit D, and constituent unit E are the same or different, and are each independently a substituted or unsubstituted alkyl group having 8 to 12 carbon atoms. The preparation process of the ultra-high temperature fluid loss reducer for cementing is as follows: First, add 200 parts by weight of deionized water into a ground three-neck flask, pass nitrogen for 30 minutes to remove oxygen in the reaction liquid, add 45 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and stir and dissolve it in a stirrer. Then, weigh 4 parts by weight of acrylic acid (AA) and add it to the ground three-neck flask for mixing and stirring. Continuously pass nitrogen, and then use a 15% by mass NaOH solution to adjust the pH value of the reaction solution to 7. Weigh 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.3 parts by weight of N,N-methylenebisacrylamide (MBA), and add them to the ground three-neck flask in sequence for mixing and stirring to obtain a mixed reaction solution. Keep stirring at a speed of 200 - 400 revolutions per minute until all monomers are completely dissolved. After stirring for a certain time, a slightly viscous liquid appears to obtain a polymer gel. Prepare an initiator solution, and add the initiator solution dropwise into the ground three-neck flask at a dropping rate of 5 - 10 mL / min. Keep the reaction temperature at 50°C - 60°C, keep nitrogen passing through, and stir and react for 4 - 6 h to end the reaction. Finally, naturally cool to obtain a colorless viscous liquid, which is the ultra-high temperature fluid loss reducer J1 prepared. The initiator used is a redox initiator system. Among them, the oxidant is ammonium persulfate, the reductant is sodium bisulfite, and the weight ratio of the amount of the oxidant to the reductant is 2:1. The amount of the initiator used is 1% by weight of the total synthetic monomers used. Example 2: This example provides an ultra-high temperature fluid loss reducer for cementing. The ultra-high temperature fluid loss reducer is prepared by the same method as in Example 1, except that: weigh 45 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.25 parts by weight of N,N-methylenebisacrylamide (MBA) according to the weight ratio. The initiator is a mixture of ammonium persulfate and sodium bisulfite, and its addition weight ratio is 2:1. The addition amount of the initiator is 1% of the total mass of the monomers. The prepared ultra-high temperature fluid loss reducer is marked as J2. Example 3: This example provides an ultra-high temperature fluid loss reducer for cementing. The ultra-high temperature fluid loss reducer is prepared by the same method as in Example 1, except that: weigh 45 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.35 parts by weight of N,N-methylenebisacrylamide (MBA) according to the weight ratio. The initiator is a mixture of ammonium persulfate and sodium bisulfite, and the addition weight ratio thereof is 2:1. The addition amount of the initiator is 1% of the total mass of the monomers. The prepared ultra-high temperature fluid loss reducer is labeled as J3. Example 4: This example provides an ultra-high temperature fluid loss reducer for well cementing. The ultra-high temperature fluid loss reducer is prepared by the same method as in Example 1, except that: 45 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.4 parts by weight of N,N-methylenebisacrylamide (MBA) are weighed according to the weight ratio. The initiator is a mixture of ammonium persulfate and sodium bisulfite, and the addition weight ratio thereof is 2:1. The addition amount of the initiator is 1% of the total mass of the monomers. The prepared ultra-high temperature fluid loss reducer is labeled as J4. Comparative Example 1: The fluid loss reducer is prepared by the same method as in Example 1, except that: N,N-methylenebisacrylamide (MBA) is not added during the preparation process to compare the influence of the addition of N,N-methylenebisacrylamide (MBA) on the performance of the fluid loss reducer. According to the weight ratio: 45 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM). The remaining synthesis steps, conditions, and types of drugs are the same as those in Example 1. The prepared ultra-high temperature fluid loss reducer is labeled as DJ1. Comparative Example 2: The fluid loss reducer is prepared by the same method as in Example 1, except that: the content of N,N-methylenebisacrylamide (MBA) is relatively high during the preparation process to compare and analyze the influence of the addition of high-specific gravity N,N-methylenebisacrylamide (MBA) on the performance of the fluid loss reducer. According to the weight ratio: 45 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.7 parts by weight of N,N-methylenebisacrylamide (MBA). The remaining synthesis steps, conditions, and types of drugs are the same as those in Example 1. The prepared ultra-high temperature fluid loss reducer is labeled as DJ2. Comparative Example 3: The fluid loss reducer was prepared in the same manner as in Example 1, except that the content of N,N-methylenebisacrylamide (MBA) was relatively low during the preparation process, and the influence of the addition of low-specific-gravity N,N-methylenebisacrylamide (MBA) on the performance of the fluid loss reducer was comparatively analyzed. According to the weight ratio: 45 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 parts by weight of acrylic acid (AA), 16 parts by weight of acrylamide (AM), 5 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.1 part by weight of N,N-methylenebisacrylamide (MBA). The remaining synthesis steps, conditions, and types of chemicals were the same as those in Example 1. The prepared ultra-high temperature fluid loss reducer was labeled as DJ3. Comparative Example 4: This comparative example provides a fluid loss reducer for well cement slurries, which is prepared by the following specific preparation method: The ultra-high temperature fluid loss reducer was prepared in the same manner as in Example 1, except that the ultra-high temperature fluid loss reducer used was a field ultra-high temperature fluid loss reducer sample, labeled as DJ4. BRIEF DESCRIPTION OF THE DRAWINGS The drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation to the present invention. In the drawings: Figure 1 It is the thickening curve graph of the cement slurry incorporated with the fluid loss reducer provided in Example 1 (the addition amount is 3% of the dry weight of cement) in Test Example 1 of the present invention at 240°C × 120 MPa. It can be seen from Figure 1 that after adding Example 1, the overall thickening curve of the cement slurry is stable, without obvious abnormal situations such as "bulges" and rapid decreases in consistency, indicating that Example 1 provided by the present invention has good temperature resistance, has good compatibility with the retarder, has little influence on the thickening process of the cement slurry, and the cement slurry can still maintain at about 20 Bc in an ultra-high temperature environment, indirectly reflecting its good settlement stability. Test Example 1: Test the rheological properties of the synthesized ultra-high temperature fluid loss reducer at room temperature and 240°C under different addition amounts of the fluid loss reducer. According to GB / T 19139-2012 "Test Methods for Oil Well Cements", SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurries", and SY / T 6466-2016 "Experimental Methods for Properties of Oil Well Cement Stone", cement slurries were prepared according to the formula, and the ultra-high temperature fluid loss reducer J1 described in Example 1 and the ultra-high temperature fluid loss reducer DJ1 prepared in Comparative Example 1 were respectively added at a mass fraction of 3-5%, and experiments were carried out at room temperature and 240°C to test the rheological properties of the cement slurries. The results are shown in Table 1. The cement slurry formula 1 is: 500 g of Jiahua G-grade cement + 50% silica sand + 4% retarder + X% fluid loss reducer + water-cement ratio of 0.44. The cement slurry formula 2 is: The difference from the cement slurry formula 1 is that the cement used is Shengwei G-grade cement. The cement slurry formula 3 is: The difference from the cement slurry formula 1 is that the cement used is Zibo G-grade cement. Table 1 Rheological properties test of cement slurry According to the experimental results in Table 1, it can be seen that: The fluid loss reducer J1 prepared in Example 1 of the present invention has good rheological properties of the cement slurry at a temperature of 240 °C, meeting the requirements of the cement slurry for ultra-high temperature cementing. Test Example 2: For Examples 1-4 and Comparative Examples 1-4, according to the relevant regulations in GB / T 19139-2012 "Test Methods for Oil Well Cement", SY / T6544-2017 "Performance Requirements for Oil Well Cement Slurry", and SY / T 6466-2016 "Experimental Methods for Properties of Oil Well Cement Stone", the compatibility of different oil well cements and synthetic ultra-high temperature fluid loss reducers under the condition of 240 °C was tested, and the results are shown in Table 2. Table 2 Influence of oil well cement on the fluid loss reduction performance of the fluid loss reducer Project J1 J2 J3 J4 DJ1 DJ2 DJ3 DJ4 Formula 1 42 43 40 43 128 132 112 138 Formula 2 42 42 39 44 127 131 113 139 Formula 3 43 41 40 44 128 132 115 138 It can be seen from Table 2 that the fluid loss reducers prepared in Examples 1-4 and Comparative Examples 1-4 of the present invention have good compatibility with different cements. Test Example 3: For Examples 1-4 and Comparative Examples 1-4, according to the relevant regulations in GB / T 19139-2012 "Test Methods for Oil Well Cement", SY / T6544-2017 "Performance Requirements for Oil Well Cement Slurry", and SY / T 6466-2016 "Experimental Methods for Properties of Oil Well Cement Stone", the ultra-high temperature fluid loss reducers prepared in Examples 1, 2, 3, 4, Comparative Examples 1, 2, 3, 4 were prepared into cement slurry according to the cement slurry API experimental standard, put into a fluid loss instrument, set the temperature at 180 - 240 °C, the pressure at 6.9 MPa, collect the filtrate within 30 min with a measuring cylinder, and multiply the observed liquid volume value by 2 to obtain the API fluid loss. If gas channeling occurs within 30 min, the fluid loss of the cement slurry should be calculated according to the formula. In the formula, V——Calculated API fluid loss, mL; V t ——Volume of collected filtrate, ml; t——Time until gas channeling occurs, min; Test its performance parameters such as the initial consistency and API water loss of the cement slurry at different experimental temperatures and dosages of fluid loss additives. The results are shown in Table 3. In the present invention, there is no specific limitation on the formulation of the cement slurry for well cementing. The formulation of the cement slurry in the case is a conventional choice in well cementing. The cement slurry system used in the experiment is Cement Slurry Formula 1. Among them, the retarder is self-made in the laboratory, which is a carboxylic acid retarder and can withstand temperatures up to 240°C. Table 3 Water loss reduction performance of fluid loss additives under different conditions As can be seen from Table 3, the fluid loss additives prepared in Examples 1-4 of the present invention have good water loss reduction performance at 180-240°C. At the same time, as the temperature increases, although the water loss of Example 1 increases to some extent, it remains good overall. At the same time, as the dosage increases, a good water loss reduction effect can be achieved when the dosage of the fluid loss additive accounts for about 4% of the cement weight. By comparing different examples, it is also found that the polymer monomers have a certain influence on the performance of the product, but the overall API water loss is less than 50 mL. Compared with the comparative examples, it can be seen that the introduction of a cross-linking agent into the quaternary polymer can effectively improve the temperature resistance of the polymer, maintain a low water loss in a super-high temperature environment, and at the same time can effectively reduce the requirement of the water loss for the polymer molecular weight and reduce the influence of the product on the fluidity of the cement slurry. Test Example 4: For Examples 1-4 and Comparative Examples 1-4, according to the test standards of compressive strength and thickening time in the national standard GB / T19139-2012 "Test Methods for Oil Well Cement", to investigate their influence on the performance of the cement slurry. The results are shown in Table 4. The compressive strength of the cement slurry system without adding fluid loss additive is 48.7 MPa, and the thickening time is 330 min. Among them, the retarder is self-made in the laboratory, which is a carboxylic acid retarder and can withstand temperatures up to 240°C. Table 4 Influence of fluid loss additives on the compressive strength and thickening time of cement As can be seen from Table 4, the fluid loss additives prepared in Examples 1-4 provided by the present invention have no obvious influence on the compressive performance and thickening time of the cement slurry, and the polymer can also participate in the strength development of the cement stone, increasing the mechanical strength of the cement stone to a certain extent. Compared with the comparative examples, after the polymer introduces a cross-linking agent, it can effectively reduce the adverse effects of the fluid loss additive on other properties of the cement slurry and ensure the performance requirements of the cement slurry in a super-high temperature environment. Test Example 5: For Example 1 and Comparative Example 1 of the ultra-high temperature fluid loss reducer for cementing provided, a cement slurry stability experiment was carried out in accordance with the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement", and the test temperature was 180-240 °C. The comparison of the settlement stability between Example 1 and Comparative Example 1 and the cement sample without adding the fluid loss reducer is shown in Table 5 below. Table 5 Cement Slurry Stability Experiment Although the disclosed embodiments of the present application are as above, the described content is only the embodiments adopted for facilitating the understanding of the present application and is not intended to limit the present application. Any person skilled in the art within the scope of the present application can make any modifications and changes in the form and details of the implementation without departing from the spirit and scope disclosed by the present application. However, the scope of patent protection of the present application shall still be subject to the scope defined by the appended claims.

Claims

1. A super high temperature fluid loss reducer for cementing, and the composition monomers of the super high temperature fluid loss reducer are: 2-acrylamido-2-methylpropanesulfonic acid (AMPS), acrylic acid (AA), acrylamide (AM), N,N-dimethylacrylamide (DMAM), N,N-methylenebisacrylamide (MBA); (1) The super high temperature fluid loss reducer contains a structural unit A shown in Formula 1, a structural unit B shown in Formula 2, a structural unit C shown in Formula 3, a structural unit D shown in Formula 4, and a structural unit E shown in Formula 5; Among them, R1, R2, R3, R4, and R5 in the constituent unit A, the constituent unit B, the constituent unit C, the constituent unit D, and the structural unit E are the same or different, and are each independently a substituted or unsubstituted alkyl group of C8-C12. (2) Among them, the method includes mixing monomer A, monomer B, monomer C, monomer D, monomer E, and deionized water in the presence of an initiator and then carrying out a copolymerization reaction. The weight parts ratio of the synthetic monomers is as follows: 40-60 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 3.0-8.0 parts of acrylic acid (AA), 15-25 parts of acrylamide (AM), 5.0-8.0 parts of N,N-dimethylacrylamide (DMAM), 0.3-0.5 part of N,N-methylenebisacrylamide (MBA); (3) First, add 150-200 parts of deionized water to a ground three-necked flask, pass nitrogen for 15-30 minutes to remove oxygen in the reaction liquid, add 40-60 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and stir and dissolve in a stirrer. Then, weigh 3.0-8.0 parts by weight of acrylic acid (AA) and add it to the ground three-necked flask for mixing and stirring. (4) Keep passing nitrogen, then use a 15% NaOH solution by mass to adjust the pH value of the reaction solution to 6-7. Weigh 15-25 parts by weight of acrylamide (AM), 5.0-8.0 parts by weight of N,N-dimethylacrylamide (DMAM), and 0.3-0.5 part of N,N-methylenebisacrylamide (MBA), and add them to the ground three-necked flask in sequence for mixing and stirring to obtain a mixed reaction solution. Keep stirring at a rotation speed of 200-400 revolutions per minute until all monomers are completely dissolved. After stirring for a certain time, a slightly viscous liquid appears to obtain a polymer gel. Prepare an initiator solution, and add the initiator solution to the ground three-necked flask at a dropping rate of 5-10 mL / min. Keep the reaction temperature at 50°C-60°C, keep nitrogen passing, and stir and react for 4-6 h to end the reaction. Finally, naturally cool to obtain a colorless viscous liquid, which is the prepared super high temperature fluid loss reducer.

2. The preparation method of the ultra-high temperature fluid loss reducer for well cementing according to claim 1, characterized in that, The total mass of the synthetic monomers is 25%-45% of the total mass of the deionized water, and the pH of the mixed solution after mixing the unit A, the unit B, the unit C, the unit D, the monomer E, and the deionized water is 6-7.

3. The preparation method of the ultra-high temperature fluid loss reducer for well cementing according to claim 1, characterized in that, The initiator adopts a redox initiation system, wherein the oxidant is at least one of persulfate, ammonium persulfate and potassium persulfate, the reductant is at least one of sodium bisulfite and ammonium hydroxide, and the weight ratio of the amount of the oxidant to the amount of the reductant is (1-3):(1-2). The amount of the initiator is 0.5-1.5% by weight of the total synthetic monomers used.

4. The preparation method of the ultra-high temperature fluid loss reducer for well cementing according to claim 1, characterized in that, The addition amount of the ultra-high temperature fluid loss reducer described accounts for 3%-5% of the weight of the cement and can withstand a temperature of 240°C.

Citation Information

Patent Citations

  • Ultrahigh-temperature modified polymer well cementation fluid loss agent as well as preparation method and application thereof

    CN113651931A

  • Preparation method of high-temperature-resistant salt-tolerant fluid loss agent composition

    CN115404061A

  • Well cementation cement fluid loss agent and preparation method thereof

    CN118620136A